The establishment of sports systems engineering (SSE) as a discipline - Sun, J. (International Journal of Sports Science and Engineering, 2007)
Through analyzing the necessity and feasibility of the establishment of Sports Systems Engineering as a discipline, this article defines the definition of Sports Systems Engineering, expounds and proves its nature, features and orientation and also builds its theory system and method system.